2018
DOI: 10.21660/2018.47.98784
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Investigation Using Resistivity Method and Drilling for Drought Mitigation in Tulungagung, Indonesia

Abstract: Research of the groundwater in Pakel, Bandung and Besuki Subdistricts, Tulungagung District has been implemented. The research area is located in the rice field area, previously an area of annual flooding inundation during the rainy season. This situation troubles the community and local government of Tulungagung District. During the dry season, the mud cracks, making it difficult as agricultural land. The research was done using Geoelectrical Resistivity Schlumberger configuration method. The measurement poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Geoelectric method measurement scheme can be seen in the following figure (Telford, et al, 1990). The relationship between measured current strength (I) with the potential difference generated (V) produces rock resistivity (ρ) can be written Legowo et al, (2018); Afandi et al, (2018); Susilo et al, (2018):…”
Section: Data Retrieval Methodsmentioning
confidence: 99%
“…Geoelectric method measurement scheme can be seen in the following figure (Telford, et al, 1990). The relationship between measured current strength (I) with the potential difference generated (V) produces rock resistivity (ρ) can be written Legowo et al, (2018); Afandi et al, (2018); Susilo et al, (2018):…”
Section: Data Retrieval Methodsmentioning
confidence: 99%
“…Berdasarkan peta kontur ini dapat ditafsirkan posisi akuifer. Metode geolistrik telah terbukti berhasil dalam survey air tanah [8] Penelitian dapat dilakukan dengan berbagai kofigurasi seperti konfigurasi. Wenner, Schlumberger, Wenner-Schlumberger, dan dipol-dipol.…”
Section: Pendahuluanunclassified
“…Based on the study of industrial well data which showed the exploitation of industrial well water was carried out at a depth of 140 to 160 meters, and cross section of the subsurface 2D, it can be concluded that the industrial wells exploited water in the aquifer layer with low resistivity between 14.7 up to 46.8 ohms (the first green to the fourth green). The low resistivity value showed potential aquifer groundwater (Susilo, Sunaryo, & Fitriah, 2018). In otherhand, drilling well monitoring was carried out to a depth of 170 meters with a filter pipe position at a depth of 142-165 meters.…”
Section: Study On Industrial Well Datamentioning
confidence: 99%